Heart rate and lactate formation during floor exercise routine in competitive young female gymnasts - Mattei, C.; Matta, D.; Cugusi, L.; Massidda, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The studies of the physiological demands during actual artistic gymnastic (AG) performance are few due to its peculiarities in duration and in nature of activities (Goswami and Gupta, 1998). In fact, the movements performed by females on the four apparatus are characterized by quick postural change causing profound effect on bodily responses (Le Marr, 1983). The aim of this study was to analyze the effects of competitive floor exercise routine on heart rate (HR) and blood lactate (BL) formation in young competitive female gymnasts. Methods: Ten young gymnasts (mean age 9.1±1.4 yrs) practicing AG at Italian Club were examined. The athletes had been gymnasts for an average of 3.2 yrs, they trained for 16.2±1.5 h/week and they were competitive at National level. The HR (bpm/min) was recorded continuously during a simulation of competition on floor using a telemetric system (Polar Team Pro). All gymnasts performed three floor routine separated each other by four minutes of passive recovery. Three finger prick samples (25 ìL) for each floor routine were collected and analyzed for BL (mmol/L) before, immediately after, and at 2 minutes (min) of rest period following exercise using a portable lactate analyzers (Arkray Lactate Pro). For the data analysis we have considered the mean parameters` values of the three routine. Results: The duration of floor exercise was 1.26±2.1 min. The mean HR during the entire routine was 176.5±16.0 bpm, with mean HR peak of 191±18.1 bpm. For the 42% of the total time of exercise, athletes maintained a very high HR (90-100% of HR max). During the remain time of the floor routine, the HR was comprised between the 80-90% and the 70-80% of the HR max. Gymnasts have produced a low-moderate BL values following each exercise (3.2 to 5.6 mmol/L), that were reverted back to basal values at 2 min rest. Discussion: Our results showed that cardiovascular load required to young gymnasts during a competitive floor exercise routine is very heavy and it is dominated by anaerobic metabolism. The data suggest the need to develop a training protocol aimed to improve the lactate tolerance of young gymnasts. It would be useful highlight the importance of improve the lactate tolerance specifically if we consider that fatigue in gymnasts is more than a simply metabolic problem, due to its correlation with a higher risk of injuries (Jemni et al., 2003), particularly on floor exercises.